EFEKTIFITAS DAN KORELASI IMPORTASI ANTIKOAGULAN PADA MASA PANDEMI COVID-19 - Eka Irmawati Achmad; Etik Sumardani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been identified as the causative agent of Coronavirus Disease 2019 (COVID-19). In severe cases, the disease is frequently accompanied by blood coagulation disorders that increase the risk of thrombotic events, impair organ function, and ultimately contribute to higher mortality. In response to these complications, anticoagulant therapies such as Heparin, Enoxaparin, Rivaroxaban, and Fondaparinux have become key components of COVID-19 patients management. This study aims to evaluate the effectiveness of anticoagulant use in patients with COVID-19 and to analyze its correlation with changes in the import profile of anticoagulant drugs and active pharmaceutical ingredients during the COVID-19 pandemic. The research method uses a descriptive analysis method using data of Import License for drugs and anticoagulant drug ingredients from the pre-pandemic period (October 2018 – February 2020) were compared with those from the pandemic period (March 2020 – July 2021. The results showed that the use of anticoagulants—particularly enoxaparin and fondaparinux— was associated with improvement of coagulation parameters, reduced risk of thromboembolic events, and lowered of mortality among COVID-19 patients. Fondaparinux was reported to be effective in preventing venous thromboembolism (VTE) and best related to its drug interaction profile. Analysis of import license data revealed a significantly increase in both number of import license and volume of imported anticoagulant, including Heparin, Enoxaparin, Rivaroxaban, and Fondaparinux during the pandemic, with the most increase observed for fondaparinux. Based on the results of this study, it highlights a clear correlation between the higher demand for anticoagulant therapy in COVID-19 patients and the increased importation of anticoagulant during the pandemic